(untitled) (Scientific journal of the Fergana State University, 2024)
The elemental composition of Peganum harmala plant root and seed samples growing in Olmaliq district of Tashkent region was studied for the first time by inductively coupled plasma mass spectrometry method on detailed ICP-MS AT 7500 equipment. 43 elements were quantitatively determined in the root and seed composition of Peganum harmala plant. It was found that there are 42 elements in the root of the plant, and 43 elements in the seed. The natural tendency of the amount of an element to decrease as its mass increases is shown. It was observed that the amount of heavy elements in the root of Peganum harmala plant is slightly higher than the amount of heavy elements in the seed. Ca > K > Fe > Mg > Na > Al > Si > S > Zn > Sr is the most common. Among the macroelements, Ca > K > Mg > Na > S predominates. Among the microelements, a large amount of Fe > Al > Si > Zn > Sr was found. The roots and seeds of the Peganumharmala plant were brought for sampling from the mountain zone of the Almalyk region and the quantitative composition of the main elements was compared.